Evaluation of models of microbial communities of plant organisms in aquatic ecosystems - Abakumova A.I., Абакумова А.И.; Ismailova A.A., Исмаилова А.А. (Рroblems of engineering and professional education, 2023)
The properties of solutions are studied in mathematical models of the dynamics of biomass of microbiological communities. The flow system model is used to study the phytoplankton community in an aquatic ecosystem. The properties of solutions coincide with the dynamics of natural communities, demonstrating the dominance of individual species in the community.